The Macroeconomics of Irreversibility - Baley, Isaac; Blanco, Andrés (Review of Economic Studies, 2026)
We study aggregate capital dynamics in an investment model with idiosyncratic productivity shocks, fixed capital adjustment costs, and irreversibility driven by a wedge between capital purchase and resale prices. We derive sufficient statistics that capture the role of investment frictions in aggregate capital fluctuations, measure these statistics using investment microdata, and exploit them to discipline the capital price wedge. Irreversibility doubles the persistence of capital fluctuations and is crucial for reconciling micro-level investment behaviour with macroeconomic propagation.